2018
DOI: 10.5195/jmla.2018.314
|View full text |Cite
|
Sign up to set email alerts
|

Publication outcome of abstracts submitted to the American Academy of Ophthalmology meeting

Abstract: ObjectiveAbstracts submitted to meetings are subject to less rigorous peer review than full-text manuscripts. This study aimed to explore the publication outcome of abstracts presented at the American Academy of Ophthalmology (AAO) annual meeting.MethodsAbstracts presented at the 2008 AAO meeting were analyzed. Each presented abstract was sought via PubMed to identify if it had been published as a full-text manuscript. The publication outcome, journal impact factor (IF), and time to publication were recorded.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
(30 reference statements)
6
22
1
Order By: Relevance
“…In our results, researches with large sample size (≥500) were published earlier, which emphasized the importance of the choosing of sample size for a study. Our study also showed the influence of funding level on publication, consistent with earlier researches . On one hand, those funded researches have been evaluated in a rigorous manner by funding party at an early stage, to verify their quality and value.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our results, researches with large sample size (≥500) were published earlier, which emphasized the importance of the choosing of sample size for a study. Our study also showed the influence of funding level on publication, consistent with earlier researches . On one hand, those funded researches have been evaluated in a rigorous manner by funding party at an early stage, to verify their quality and value.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also showed the influence of funding level on publication, consistent with earlier researches. 13,18 On one hand, those funded researches have been evaluated in a rigorous manner by funding party at an early stage, to verify their quality and value. On the other hand, authors could carry out their research programme more smoothly with ample funds supported.…”
Section: F I G U R E 3 Publication Rate By Conference Yearmentioning
confidence: 99%
“…The majority of first authors were from North America (43.9%, n=764), which showed a significant 5 year conversion rate of 50.5% (n=386), slightly lower than Oceania (57.1%, n=24). However, as recently described by Mimouni M and colleagues analyzing the fate of the 2008 AAO abstracts, 14 the North American abstracts were associated with the highest median IF of publication (3.40). As already suggested, 14 this might be due to larger availability of resources for US researchers or to the language barrier.…”
Section: Discussionmentioning
confidence: 68%
“…Literature investigated several factors potentially associated with publication including: reporting only positive results and data from randomized controlled trials, large sample size, oral presentation, basic science, higher quality, multicentricity, pharmaceutical funding and accademic affiliation. 1,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the present study, conference, presentation type and topic all showed to be associated with publication rates. (Table 4) In fact, the ARVO meeting was associated with the highest 2-year (36.1%) and 5-year (51.9%) publication rates; the abstracts presented as paper (oral) presentation had the highest 2-year (44.5%) and 5-year (60.5%) publication rates; and Basic science had the highest 5 year (52.1%) publication rates.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation